A beneficial fungal root endophyte triggers systemic RNA silencing and DNA methylation of a host reporter gene. Issue 1 (31st December 2023) - Dalakouras, Athanasios; Katsaouni, Afrodite; Avramidou, Marianna; Dadami, Elena; Tsiouri, Olga; Vasileiadis, Sotirios; Makris, Athanasios; Georgopoulou, Maria Eleni; Papadopoulou, Kalliope K.
ABSTRACT: A growing body of evidence suggests that RNA interference (RNAi) plays a pivotal role in the communication between plants and pathogenic fungi, where a bi-directional trans-kingdom RNAi is established to the advantage of either the host or the pathogen. Similar mechanisms acting during plant association with non-pathogenic symbiotic microorganisms have been elusive to this date. To determine whether root endophytes can induce systemic RNAi responses to their host plants, we designed an experimental reporter-based system consisting of the root-restricted, beneficial fungal endophyte, Fusarium solani strain K (FsK) and its host Nicotiana benthamiana . Since not all fungi encode the RNAi machinery, we first needed to validate that FsK does so, by identifying its core RNAi enzymes (2 Dicer-like genes, 2 Argonautes and 4 RNA-dependent RNA polymerases) and by showing its susceptibility to in vitro RNAi upon exogenous application of double stranded RNAs (dsRNAs). Upon establishing this, we transformed FsK with a hairpin RNA (hpRNA) construct designed to target a reporter gene in its host N. benthamiana . The hpRNA was processed by FsK RNAi machinery predominantly into 21–24-nt small RNAs that triggered RNA silencing but not DNA methylation in the fungal hyphae. Importantly, when the hpRNA-expressing FsK was used to inoculate N. benthamiana, systemic RNA silencing and DNA methylation of the host reporter gene was recorded. Our data suggest that RNAi signals can be translocated by root endophytes to their hosts and can modulate gene expression during mutualism, which may be translated to beneficial phenotypes.